Effect of oscillation modes on weld formation and pores of laser welding in the horizontal position. (February 2023) - Wu, Manpeng; Luo, Zhen; Li, Yang; Liu, Lihua; Ao, Sansan
Highlights: Three types of the oscillation patterns were investigated to HSLA steel in the horizontal position. The circular oscillation pattern significantly affects the elimination of bubbles and suppresses pores. The circular oscillation laser welding changes the energy distribution law. Abstract: The present paper systematically investigated the effect of oscillation modes on weld formation and pores of laser welding for high-strength low alloy (HSLA) steel in the horizontal position. The laser energy distributions with different oscillation modes were calculated and analyzed. The vapor plume, the molten pool characteristic, and the keyhole behavior with different oscillation modes were observed. The experimental results show that compared with non-oscillation laser welding and lateral oscillation laser welding, circular oscillation laser welding has more uniform energy distribution, less fluctuation of laser spot motion velocity, and more stable plume and keyhole. Circular oscillation laser welding decreases the depth-to-width ratio of the welds, reduces welding spatters, and improves weld formation. Circular oscillation of the laser beam increases keyhole size, and the oscillation keyhole formed is more likely to trap the bubbles in the molten pool, thus reducing the probability of pore formation. Finally, circular oscillation laser welding with an oscillation amplitude of 4 mm and an oscillation frequency of 60 Hz obtains high-quality weld with expected morphology and free of pores.